CYBER COUNSELING TO IMPROVE SCHOOL GUIDANCE AND COUNSELING SERVICES IN PRIMARY AND SECONDARY EDUCATION - Hasgimianti; Raja Rahima Munawarah Raja Ahmad; Suci Habibah; Nur’Aini Safitri (EDUCATIONE, 2026)
This scoping review examines what is known about the effectiveness, implementation models, challenges, and counselor competencies related to cyber counseling in primary and secondary school guidance services. A literature search was conducted in Scopus, ERIC, ScienceDirect, Google Scholar, SINTA, and Garuda for studies published between 2015 and 2025 using keywords such as “cyber counseling,” “online counseling,” and “digital school counseling.” The search, completed in January 2026, identified 124 records; after screening based on predefined criteria, 20 peer-reviewed articles were analyzed. Data were synthesized using thematic content analysis. Findings indicate that cyber counseling improves access and student participation through flexible communication formats, but its implementation faces barriers related to infrastructure, counselor digital competence, and ethical and data security issues. The literature also shows heterogeneous study designs and limited contextual coverage, which restrict generalizability. This review highlights the need for structured counselor training and supportive school policies for responsible integration of cyber counseling.